Центральные расширения *-алгебр измеримых операторов - Муратов, М.А.; Чилин, В.И. (Видавничий дім "Академперіодика" НАН України, 2009)
Описано новi класи заповнених *-пiдалгебр у *-алгебрi LS(M) локально вимiрних операторiв, приєднаних до алгебри Неймана M. Зокрема, введено *-алгебру LS(M, τ) τ-локально вимiрних операторiв, що асоцiйована з точним нормальним напiвскiнченним слiдом τ на M. Показано, що для алгебри Неймана M з σ-скiнченним центром, а також для алгебр Неймана типу I *-алгебри LS(M, τ) та LS(M) збiгаються. У випадку алгебр Неймана типу II з не σ-скiнченним центром *-алгебра LS(M, τ) iстотно вужча, нiж *-алгебра LS(M). New classes of solid *-subalgebras in an *-algebra LS(M) of locally measurable operators affiliated to a von Neumann algebra M are considered. In particular, an *-algebra LS(M, τ) of τ-locally measurable operators, which is associated with a faithful normal semiinfinite trace is introduced. It is proved that the *-algebra LS(M, τ) and LS(M) coincide, if the center of von Neumann algebras is σ-finite or the von Neumann algebra is of type I. If the von Neumann algebra is of type II with non σ-finite center, then the *-algebra LS(M, τ) is more slender that the *-algebra LS(M).